1999
DOI: 10.1046/j.1365-2389.1999.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maize straw placement on mineralization of C and N in soil particle size fractions

Abstract: Summary Fundamental knowledge about the complex processes during the decomposition, mineralization and transfer of residue organic matter in soils is essential to assess risks of changes in agricultural practices. In a double tracer (13C, 15N) experiment the effect of maize straw on the mineralization dynamics and on the distribution of maize‐derived organic matter within particle size fractions was investigated. Maize straw (a C4 plant) labelled with 15N was added to soils (13.2 g dry matter kg–1 soil) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 30 publications
3
57
1
1
Order By: Relevance
“…This pattern, which may be caused because fine fractions in soil have high surface area which can enhance formation of organo-mineral complexes that protect SOM from microbial degradation (Hassink, 1997;Zhang and Liu, 2010), supports previous findings that soil fractionation is a useful tool for examining different C and N pools in soil (Amelung et al, 1998;Gerzabek et al, 2001;Stemmer et al, 1999). Across the transect, we observed that C and N concentrations and stocks in bulk soils were negatively correlated with sand content and positively correlated with silt and clay contents.…”
Section: Discussionsupporting
confidence: 86%
“…This pattern, which may be caused because fine fractions in soil have high surface area which can enhance formation of organo-mineral complexes that protect SOM from microbial degradation (Hassink, 1997;Zhang and Liu, 2010), supports previous findings that soil fractionation is a useful tool for examining different C and N pools in soil (Amelung et al, 1998;Gerzabek et al, 2001;Stemmer et al, 1999). Across the transect, we observed that C and N concentrations and stocks in bulk soils were negatively correlated with sand content and positively correlated with silt and clay contents.…”
Section: Discussionsupporting
confidence: 86%
“…Li et al (2001) reported straw decomposition rates were closely related to SI depths, in decreasing order from 5 to 15 cm to the surface soil. Thus, compared with NT, tillage treatments have increased the potential to promote straw C conversion into soil C (Stemmer et al 1999;Wingeyer et al 2012). It is noteworthy that NT treatment generally results in greater soil C storage than PT and RT treatments at surface soil (Bossuyt et al 2002;Dolan et al 2006;Huggins et al 2007;Hermle et al 2008).…”
Section: Si Effects On Soil Cmentioning
confidence: 99%
“…Second, many reports concluded that SOC concentration of different aggregates was higher for NT and RT (ridge tillage, similar to DT) compared with PT in the depth of 0-5 cm, nevertheless, the inverse effects was found in the depth of 5-20 cm or 10-15 cm (Six et al, 1999;Zibilske and Bradford, 2007). Similar researches deduced that more SOC concentration from the maize conveyed into the stable SOC in tilled soil than untilled soil, and favoring formation in the micro-aggregates (Stemmer et al, 1999).…”
Section: Tillage Impacts On Socmentioning
confidence: 86%